Pengenalan Pesawat Terbang Tingkat Dasar Bagi Mahasiswa Perguruan Tinggi Di Banyuwangi - Prayitno, Hadi; Dimas Hari Cahyo; Arief Rusdyansyah; Fajar Islam; Dimas Endrawan Putra; Muhammad Nur Cahyo Hidayat Nasrullah (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Aviation safety is a condition where safety requirements are met in the use of airspace. Technological developments in the world of aviation will influence the risk of aircraft accidents occurring in the world of aviation, so the level of Standard Operation Procedure (SOP) of an airline must also be considered. Currently, limited information regarding aviation by university students outside of aviation schools is a problem often faced in the aviation industry. It does not rule out the possibility that those who have a career or work in the aviation industry are students from aviation or aviation schools, while those from universities outside of aviation will not be competent in it. Research regarding the introduction of basic level aircraft for university students in Banyuwangi was carried out to share knowledge with students who have chosen education outside the field of aviation. Where later he will become an informant for family, relatives and the surrounding community who are still at senior high school level as an option for them and their parents in determining their future education. And for those who have taken university level, they can get information or knowledge in the aviation field, where if they are interested, they will be able to continue their education and work in the aviation field after completing their education. This research uses qualitative methods so that the results obtained by introducing basic level aircraft for students can capture the interests and talents of university students and students to join the Banyuwangi Indonesian Aviation Academy, students will gain more in-depth knowledge about the world of aviation. Students can understand the complexities and challenges faced by pilots and other aviation professionals. They will also learn about the various stages of education and training required to achieve success in this field.